Fatigue responses in exercise under control of V O2 - Lepretre, P.-M.; Lopes, P.; Koralsztein, J. P.; Billat, V. (International Journal of Sports Medicine, 2008)
To examine the fatigue response during an exhaustive heavy exercise performed under control of oxygen uptake (SS@V·O2?50) or power output (SS@p?50), eleven trained male subjects performed an incremental test to determine the peak of the oxygen uptake value (V·O2peak) and lactate threshold and two exhaustive steady-state cycling exercises at the intermediate value between the lactate threshold and V·O2peak (SS@V·O2?50 and SS@p?50). The control of V·O2 induced an oscillation of the power output, which lowered the average power output (276 ± 47 vs. 315 ± 40 W, p = 0.004) and cancelled the slow component of oxygen kinetics. However, all subjects reached maximal cardiac output (CO) and heart rate (HR) values which were sustained almost two times longer in SS@V·O2?50 compared to SS@p?50 (979 ± 854 vs. 475 ± 236 s, p = 0.046 for CO and 1050 ± 890 vs. 513 ± 288 s, p = 0.037 for HR). Furthermore, SS@p?50 elicited V·O2peak but not SS@V·O2?50 (4963 ± 434 vs. 4723 ± 460 mL · min-1, p = 0.026). Finally, the time spent at the maximal CO and HR values is correlated with time to exhaustion at V·O2?50. In conclusion, the cause of fatigue does not seem to have the same origin during exhaustive supra-lactate threshold exercise under control of V·O2 (V·O2?50) compared to constant power output (p?50), while both elicit the maximal HR and CO values.